Epidemiology of alcohol use disorder in the general population of Togo and Benin: the ALCOTRANS study - (:unkn) unknown (My University, 2024)
Abstract Introduction Access to data concerning mental health, particularly alcohol use disorders (AUD), in sub-Saharan Africa is very limited. This study aimed to estimate AUD prevalence and identify the associated factors in Togo and Benin. Methods A cross-sectional study was conducted between April and May 2022, targeting individuals aged 18 years and above in the Yoto commune of Togo and the Lalo commune of Benin. Subjects were recruited using a multi-stage random sampling technique. AUD diagnoses were made using the MINI adapted to DSM-5 criteria. Our study collected sociodemographic information, data on psychiatric comorbidities, stigmatization, and assessed cravings, using a series of scales. The association between AUD and various factors was analyzed using multivariable logistic regression. Results In Togo, 55 of the 445 people investigated had AUD (12.4%; [95% CI: 9.5-15.7%]). Among them, 39 (70.9%) had severe AUD and the main associated comorbidities were suicidal risk (36.4%), and major depressive disorder (16.4%). Associated factors with AUD were male gender (aOR: 11.3; [95% CI: 4.8–26.7]), a higher Hamilton Depression Rating Scale (HDRS) score (aOR: 1.2; [95% CI: 1.1–1.3]) and a lower Stigma score measured by the Explanatory Model Interview Catalogue (EMIC) (aOR: 0.9; [95% CI: 0.8–0.9). The stigma scores reflect perceived societal stigma towards individuals with AUD. In Benin, 38 of the 435 people investigated had AUD (8.7%; [95% CI: 6.4–11.7]), and the main associated comorbidities were suicidal risk (18.4%), tobacco use disorder (13.2%) and major depressive episode (16.4%). Associated factors with AUD were male gender (aOR: 6.4; [95% CI: 2.4–17.0]), major depressive disorder (aOR: 21.0; [95% CI: 1.5-289.8]), suicidal risk (aOR: 3.7; [95% CI: 1.2–11.3]), a lower Frontal Assessment Battery (FAB) score (aOR:0.8; [95% CI: 0.8–0.9]) and a lower perceived stigma score (by EMIC )(aOR: 0.9; [95% CI: 0.8–0.9]). Conclusion In thes
Keywords: African Research